2019
DOI: 10.3389/fbioe.2019.00125
|View full text |Cite
|
Sign up to set email alerts
|

Glandular Segmentation of Prostate Cancer: An Illustration of How the Choice of Histopathological Stain Is One Key to Success for Computational Pathology

Abstract: Digital pathology offers the potential for computer-aided diagnosis, significantly reducing the pathologists' workload and paving the way for accurate prognostication with reduced inter-and intra-observer variations. But successful computer-based analysis requires careful tissue preparation and image acquisition to keep color and intensity variations to a minimum. While the human eye may recognize prostate glands with significant color and intensity variations, a computer algorithm may fail under such conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…2 A). Hematoxylin-eosin (HE) staining mainly distinguishes normal and abnormal cells by the morphology and size of the nucleus [ 31 ]. H1975 cells could be found in the brain of zebrafish at almost single cell resolution (white arrows).…”
Section: Resultsmentioning
confidence: 99%
“…2 A). Hematoxylin-eosin (HE) staining mainly distinguishes normal and abnormal cells by the morphology and size of the nucleus [ 31 ]. H1975 cells could be found in the brain of zebrafish at almost single cell resolution (white arrows).…”
Section: Resultsmentioning
confidence: 99%
“…One study of prostate neoplasia identification achieved favourable results by requiring that all specimens be prepared and stained by the exact same method. 11 It is intuitive that strict control over a standardised preparation process would allow for optimisation of any CNN-created model. In the absence of such a standard, more extensive training on more samples of differing types will be required.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the reliability of AI algorithms is questionable for other benign or malignant conditions encountered for which the AI algorithm was not trained. 52,53 This can lead to missed diagnosis. Human supervision can resolve this issue.…”
Section: Lack Of Accountability: Diagnostic Issues Related To Inheren...mentioning
confidence: 99%
“…Such factors include variations in the image quality, staining methods, staining times, types of scanners used for digitization, and file formats of images, which could affect the performance of AI tools. [9][10][11][12][43][44][45][46][47][48][49][50][51][52][53][54] Differences in the performance of AI algorithms in the test sets as compared with training sets in different settings, such as internal versus external sets, are the proofs of such effects. In a recent study by Eloy et al, 36 scanning error was the single most important identified in the retrospective review of discrepant cases of prostate cancer on biopsies.…”
Section: Factors Affecting Performance Of Ai Tools: Quality Of Input ...mentioning
confidence: 99%